KEARIFAN LOKAL ORANG JAWA DALAM METAFORA NOVEL PARA PRIYAYI, KARYA UMAR KAYAM - Ari Wulandari (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2017)
The metaphor is born because of the limitations of human language, while the human mind is unlimited. This research data is a metaphor in the Para Priyayi novel. This study uses a qualitative research design or research context. Metaphors are covered depends context of existing metaphors in the Para Priyayi novel. Metaphoric consists of nine patterns, namely (1) one sentence, one metaphor, (2) one sentence, two metaphors, (3) one sentence, three metaphors, (4) tenor at the front, the vehicle in the behind, (5) vehicle at the front, tenor in the behind, (6) noun - verb, (7) verb - noun, (8) noun - adjective, and (9) the frozen form. As there are four kinds of metaphor, namely (1) a metaphor of man, (2) a metaphor of animal, (3) a metaphor of plant, and (4) a metaphor of natural circumstances. The sphere of life that exists in the Para Priyayi novel metaphor includes five programs: (1) economics, (2) the family, (3) community, (4) the natural environment, and (5) of religion and belief. The values of local wisdom includes nine things, namely (1) character, (2) ethics, (3) chivalry, (4) the concept of Manunggaling Kawula kalawan Gusti, (5) education, (6) the attitude of the community, (7) moral education, (8) self-control, and (9) leadership. The research proves that metaphor in the Para Priyayi novel has certain forms and types, contains the realm of Javanese life, and the values of Java local wisdom.